PENGARUH MODEL PEMBELAJARAN KOOPERATIF DENGAN BANTUAN MEDIA TULANG NAPIER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD IT DINIYAH PEKANBARU - Wulan Winanda; Zetra Hainul Putra; Zufriady Zufriady (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2020)
The background of this research is less active students in the learning process. This study aims to determine the effect of cooperative learning models with the help of Napier bone media on mathematics learning outcomes in multiplication operations of third grade students at SD IT Diniyah Pekanbaru. The subjects of this study were 21 third grade students. The method in this study was pre-experimental using one group pretest posttest design. In this study data were collected using tests that were the initial test (pretest) and the final test (posttest). Based on the results of the hypothesis test obtained t_count = 15.9609 ≥ t_table = 1.7247. It can be concluded that there is an effect of applying cooperative learning models with the help of Napier bone media on mathematics learning outcomes in multiplication operations of third grade students of SD IT Diniyah Pekanbaru.